Estrogens in female thyroid cancer: alteration of urinary profiles in pre- and post-operative cases - Lee, SH; Kim, KM; Jung, BH; Chung, WY; Park, CS; Chung, BC (ELSEVIER SCI IRELAND LTD, 2003)
To evaluate the potential effect of estrogens in premenopausal female thyroid cancer, the concentrations of 14 estrogens were quantitatively determined in the urine of pre- and post-operative patients with thyroid papillary cancer (18 patients case, 26 similar to 54 years) and normal female subjects (20 cases, 31 similar to 52 years). The highly sensitive gas chromatography-mass spectrometry-selected ion-monitoring method was used for estrogens analysis. And an estrogen-oxidative metabolism and 16alpha-hydroxyestrone to 2-hydroxyestrone (16alpha-OH E1/2-OH El) which is the two primary and competing site of estrogen-oxidation, were determined. Catechol estrogens, including 2-OH E1, were also increased without significant changes of the other estrogen metabolites in pre-operative patients with thyroid papillary cancer compared with normal subjects. The lowest mean value of 16alpha-OH E1/2-OH E1 was remarked in pre-operative patients, and it was significantly different from the ratio of post-operative cases. As a result, it is suggested that the increase of 2-hydroxylation in estrogen metabolism may have a significant association with female thyroid cancer. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: BREAST-CANCER; RECEPTORS; ESTRADIOL; WOMEN